2021
DOI: 10.1093/bjsopen/zrab061
|View full text |Cite
|
Sign up to set email alerts
|

Spatioregional assessment of the gut microbiota in experimental necrotizing pancreatitis

Abstract: Background Infectious complications following experimental pancreatitis involve major disruptions in the gut microbiota. The aim of this study was to characterize this disruption by examining the spatioregional distribution in microbial community structure and function following experimental pancreatitis associated with pancreatic infection. Methods Mice were subjected to infusion of the pancreatic duct with either taurochola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Specifically, at the phylum level, significant differences in abundance were found for p_Verrucomicrobiota, p_Desulfobacterota, p_Fusobacteriota, p_Actinobacteriota, p_Proteobacteria, p_Euryarchaeota, and p_Nitrosp Seven species et al At the genus level, a total of 86 species showed significant differences between these two groups; while at the species level, 85 species exhibited significant variations. To gain deeper insights into these distinctions, we conducted PCA (principal component analysis) and PCoA (principal coordinate analysis) Increasing evidence has demonstrated that the composition of the intestinal microbiome differs between healthy and diseased states, and an imbalanced microbiome can contribute to alterations in the pathophysiology of gastrointestinal diseases as well as extraintestinal conditions such as pancreatitis [10]. Furthermore, metabolites derived from gut microbiota play a crucial role in the progression of acute pancreatitis (AP), with some exerting beneficial effects while others exhibiting harmful properties.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, at the phylum level, significant differences in abundance were found for p_Verrucomicrobiota, p_Desulfobacterota, p_Fusobacteriota, p_Actinobacteriota, p_Proteobacteria, p_Euryarchaeota, and p_Nitrosp Seven species et al At the genus level, a total of 86 species showed significant differences between these two groups; while at the species level, 85 species exhibited significant variations. To gain deeper insights into these distinctions, we conducted PCA (principal component analysis) and PCoA (principal coordinate analysis) Increasing evidence has demonstrated that the composition of the intestinal microbiome differs between healthy and diseased states, and an imbalanced microbiome can contribute to alterations in the pathophysiology of gastrointestinal diseases as well as extraintestinal conditions such as pancreatitis [10]. Furthermore, metabolites derived from gut microbiota play a crucial role in the progression of acute pancreatitis (AP), with some exerting beneficial effects while others exhibiting harmful properties.…”
Section: Resultsmentioning
confidence: 99%
“…muciniphila and metabolic diseases including HIV [ 5 ] and several cancers [ 8 10 , 39 ], and high abundances of A . muciniphila have also been associated with colitis and metabolic syndrome [ 47 ] and pancreatitis in mice [ 48 ]. As A .…”
Section: Discussionmentioning
confidence: 99%
“…A. muciniphila abundance is also associated with necrotizing pancreatitis, irritable bowel syndrome (IBS), diverticular disease, and drug-induced liver injury. The abundance of A. muciniphila is significantly higher in patients with necrotizing pancreatitis than in healthy controls [ 141 ]. A. muciniphila abundance in symptomatic uncomplicated diverticular disease (SUDD) and asymptomatic diverticulosis is significantly higher than that in healthy controls [ 142 ].…”
Section: The Role Of a Muciniphila In Diseasementioning
confidence: 99%